2004
DOI: 10.1606/1044-3894.239
|View full text |Cite
|
Sign up to set email alerts
|

Common Factors in Psychotherapy Outcome: Meta-Analytic Findings and Their Implications for Practice and Research

Abstract: R ecently the National Association of Social Workers (NASW) (O'Neill, 1999), citing federal statistics, reported that social workers provide more mental health services than do professionals from all other disciplines combined. A large percentage of these social work services consists of psychotherapy. Despite the widespread use of psychotherapy, consumers, researchers, and payers nonetheless question that it produces change. Indeed, in this era of managed care and diminishing financial support for mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 39 publications
0
59
0
3
Order By: Relevance
“…However, as we move firmly into the second century of this field, there is greater interest and activity in the integration of various theories and methods of psychotherapy. The Common Factors movement, which has been part of this change as research in psychotherapy, has found that psychotherapy effectiveness has relatively little to do with particular theoretical approaches to treatment but more with a set of client and therapist qualities that can be common to any particular approach to therapy (Drisko, 2004). It is becoming increasingly difficult to be considered an open-minded, unbiased, and ultimately professional and effective practitioner without taking into account and acting upon various ideas, findings, and techniques that are applicable to a particular client, and not be too focused on one particular theory of psychotherapy.…”
Section: Integrationmentioning
confidence: 99%
“…However, as we move firmly into the second century of this field, there is greater interest and activity in the integration of various theories and methods of psychotherapy. The Common Factors movement, which has been part of this change as research in psychotherapy, has found that psychotherapy effectiveness has relatively little to do with particular theoretical approaches to treatment but more with a set of client and therapist qualities that can be common to any particular approach to therapy (Drisko, 2004). It is becoming increasingly difficult to be considered an open-minded, unbiased, and ultimately professional and effective practitioner without taking into account and acting upon various ideas, findings, and techniques that are applicable to a particular client, and not be too focused on one particular theory of psychotherapy.…”
Section: Integrationmentioning
confidence: 99%
“…Furthermore, research in the field of psychotherapy has long established the importance of the therapeutic relationship on client outcomes (Drisko, 2004). Notably, one review of the psychotherapy literature by Lambert estimates that the therapeutic relationship is responsible for 30% of the variance in client outcome, second only to extra-therapeutic factors, such as client motivation to change, at 40% (Lambert, 1992as cited in Drisko, 2004.…”
Section: Professional Suitability and The Helping Relationshipmentioning
confidence: 99%
“…Lambert included factors that are part of the individual client and factors that are part of the environment (Lambert, 1992, p. 97). Drisko (2004) in turn criticises Lambert for ignoring the impact of policy and agency contexts within the extra-therapeutic. He proposes an alternative trifold scheme: the policy and agency context, the client's context, and the client as a common factor (her/his personality and personal resources) (Drisko, 2004, p. 85).…”
Section: Clients' Engagement In Everyday Life and Therapymentioning
confidence: 99%